Complementing the Self-Determination Theory With the Need for Novelty: Motivation and Intention to Be Physically Active in Physical Education Students - Fernández-Espínola, Carlos; Almagro, Bartolomé J.; Tamayo-Fajardo, Javier A.; Sáenz-López, Pedro (Frontiers in Psychology, 2020)
The theoretical framework of the Self-Determination Theory establishes that the satisfaction of basic psychological needs and more self-determined motivational forms are related to positive behavioural consequences and, therefore, may increase the intention to be physically active in Physical Education students. In this sense, the need for novelty has been proposed as a psychological need by recent scientific evidence, so it is necessary to prove its possible contribution to the prediction of young people's behaviour. Therefore, the main objective of the study was to test a model that analysed the power of prediction of the satisfaction of the needs for autonomy, competence, relatedness and novelty as well as the motivation experienced in Physical Education on the intention to be physically active. A questionnaire was administered to 1665 Physical Education students with an average age of 12.43 years (SD = 1.87), of which 835 were boys and 830 girls. An adaptation of the Spanish educational context of the Psychological Needs in Exercise Scale (BPNES) that includes the need for novelty, the Perceived Locus of Causality Scale (PLOC) and the Intention to be Physically Active Scale (IPAS) were used. Path analysis results showed that the satisfaction of the psychological needs for autonomy, competence, relatedness and novelty predicted autonomous motivation. On the other hand, the need for autonomy positively predicted controlled motivation, while the satisfaction of relatedness did so negatively. The need for competence and autonomous motivation positively predicted the intention to be physically active in Physical Education students, obtaining an explained variance of 33%. However, autonomous motivation was not related in a statistically significant way to the intention to be physically active. In conclusion, the results of the hypothesised model highlight the importance of satisfying all the basic psychological needs (including novelty) and give special emphasis to the need for competence, since it predicts autonomous motivation and the intention to be physically active outside of the educational context.